Creation and the Absolute (Some Specific Features of Pascal’s Philosophy) - Gaižutis, Algridas (Problemos, 1983)
Blaise Pascal’s contribution to natural sciences and philosophy is considered in the article. Although Pascalian axiology was limited from the historical point of view (he regarded as supreme value the values of the Christian faith, conceived both intuitively and ecstatically), it was conducive, however, to a more profound comprehension of the philosophical problem of man. The motives of Pascalian philosophy, such as moral perfection of man and versatility of his spiritual and creative abilities, are of considerable importance for the present.